Gas-on-gas competition in Shanghai - Manuhutu, Chassty; Owen, Anthony (Elsevier Science Ltd., 2010)
In common with other major economic centres in China, Shanghai's energy consumption has been increasing rapidly to support the high growth rate of its economy. To achieve rational, efficient and clean use of energy, together with improved environmental quality within the city, the Shanghai municipal government has decided to expand the supply and utilization of natural gas. Shanghai plans to increase the share of natural gas in its primary energy mix to 7 per cent by 2010, up from 3 per cent in 2005. This increase in natural gas demand has to be matched with a corresponding increase in supply. To date, the Shanghai region has relied on offshore extracted natural gas but this supply is limited due to the size of the reserves. Since 2005, the West–East pipeline has provided an alternative for Shanghai but demands from other regions could reduce the potential for expanding supplies from that source. Since domestic production will not be sufficient to meet demand in the near future, Shanghai is building a liquefied natural gas (LNG) regasification terminal at the Yangshan deep-water port that would allow an additional supply of more than 3 billion cubic meters per year of natural gas.Malaysia has already committed to supply LNG to the Shanghai terminal at a price that is significantly higher than the wholesale “city-gate” price for natural gas transported via pipeline, but still lower than the gas price to end-use consumers. The presence of both an LNG terminal and a transmission pipeline that connects Shanghai to domestic gas-producing regions will create gas-on-gas competition. This study assesses the benefits of introducing such competition to one of China's most advanced cities under various scenarios for demand growth. In this paper, the impact of imported LNG on market concentration in Shanghai's gas market will be analysed using the Herfindahl–Hirschmann index (HHI) and the residual supply index (RSI). Our results show that Shanghai remains a supply-constrained gas market that will continue to rely upon gas supplies from the western provinces and imported LNG. After 2017, the gas market in Shanghai can be regarded as unconcentrated since its HHI fall below 1800 under a very high growth scenario. In terms of RSI, the gas market can be considered competitive at low, moderate and high growth consumption between 2012 and 2015.